Muslim Tatars of the Nekrashun Parish: History and Modernity - Svetlana V. Gribova; Sergei A. Miskiewicz (Publishing house "Sreda", 2022)
The article follows the Nekrashun parish of Tatar-Muslim origin on various deep historical processes, from its origin to the present day. The purpose of the article is the observe features of the social and cultural life of the Tatars of the Nekrashun parish, to consider the role of Islamic traditions and the local mosque in the life of the population. The material for the study was the information revealed in the Lithuanian State Historical Archive, in the archive of the Grodno State Museum of the History of Religion. Much attention is paid to genealogy as a method of historical research, personal history. The work provides biographical information of imams, muezzins, active figures of the Tatar community.The authors analyze the historical stage of the infection of the Nekrashun parish in the period from the 15th-16th centuries to the present day, special attention is paid to the interwar period of infection of the twentieth century. It was revealed that Nekrashun people and its outskirts were the site of an ancient settlement of the Tatar-Muslims in the Belarusian lands. The time of the most active development of the Nekrashun parish was the interwar period, accompanied by the development of the policy of the Polish state. At that time, the mosque, which was destroyed during the First World War, was rebuilt, a Muslim school and a parish house were builded. The mosque is about high density for the local Tatar-Muslim population. It performed a consolidating function, leading to the preservation of the Tatar community. Religion is a consequence of the emergency, preventing the assimilation of the population living in an integral Muslim environment.